Flexible power point tracking for solar photovoltaic systems using secant method - Kumaresan, Anusha (2021)
Grid-connected photovoltaic (PV) systems impose challenges like voltage fluctuations, low system inertia, and power quality issues. The need to tackle these challenges led to the introduction of flexible power point tracking (FPPT), where the PV power output is controlled by an energy management system, rather than solely operating the PV systems on the maximum power point. The requirement of fast transient response implies that algorithms such as the one proposed in this article are desirable. The proposed algorithm uses the secant method to achieve significantly improved results in comparison to the existing methods. The method also simplifies the prediction of variations during changes in the environment and power reference, hence, results in reduced oscillation around the set-point and faster convergence. Experimental validation is presented in this article for supporting the claims. The results in terms of accuracy, convergence rate, steady-state oscillations, and cumulative error are bench-marked against one of the most recent FPPT methods.